The situation of farm workers in Marondera district in Zimbabwe after the fast track land reform programme (2000-2015) - Mahachi, Tichakunda (Midlands State University, 2017)
This study is aimed at exploring the plight of farm workers in Marondera district in Zimbabwe (2000-2013). The study will focus on the how the fast track land reform programme intensified problems which farm workers have been experiencing, which dates back to the colonial period. The study will focus on how the working conditions and living conditions of farm workers after the fast track land reform programme, looking at the poor wages their given, lack of job security, poor and overcrowded accommodations services, food shortages, poor basic social services. It will unearth some of the challenges brought by the structural adjustment programme (ESAP) to the farm workers. The study will go on to reach on the intervention strategies employed by the government and nongovernmental organisations in trying to alleviate the plight of farm workers in Marondera district. The study will highlight on the areas of interest by these different organisations in trying to alleviate the plight of farm workers. The study will go on to look at the coping strategies by the farm workers in order to insure their survival and uplift their living standards. The effectiveness of the intervention strategies designed by the government and NGOs would be looked at in the bid to end the plight of farm workers in the district. Also the effectiveness of the coping strategies by farm workers would be focused on. In the study primary sources such as interviews, questionnaires were used and also secondary sources as well, in order to give a sound research.